Consequences of a high incidence of microsatellite instability and BRAF‐mutated tumors: A population‐based cohort of metastatic colorectal cancer patients. (9th May 2019) - Aasebø, Kristine Ø.; Dragomir, Anca; Sundström, Magnus; Mezheyeuski, Artur; Edqvist, Per‐Henrik; Eide, Geir Egil; Ponten, Fredrik; Pfeiffer, Per; Glimelius, Bengt; Sorbye, Halfdan
Abstract: Background: Immunotherapy for patients with microsatellite‐instable (MSI‐H) tumors or BRAF ‐inhibitors combination treatment for BRAF‐ mutated (mut BRAF) tumors in metastatic colorectal cancer (mCRC) is promising, but the frequency of these molecular changes in trial patients are low. Unselected population‐based studies of these molecular changes are warranted. Methods: A population‐based cohort of 798 mCRC patients in Scandinavia was studied. Patient and molecular tumor characteristics, overall survival (OS) and progression‐free survival (PFS) were estimated. Results: Here, 40/583 (7%) tumor samples were MSI‐H and 120/591 (20%) were mut BRAF ; 87% of MSI‐H tumors were mut BRAF (non‐Lynch) . Elderly (>75 years) had more often MSI‐H (10% vs 6%) and MSI‐H/mut BRAF (9% vs 4%) tumors. Response rate (5% vs 44%), PFS (4 vs 8 months), and OS (9 vs 18 months) after first‐line chemotherapy was all significantly lower in patients with MSI‐H compared to patients with microsatellite stable tumors. MSI‐H and mut BRAF were both independent poor prognostic predictors for OS ( P  = 0.049, P  < 0.001) and PFS ( P  = 0.045, P  = 0.005) after first‐line chemotherapy. Patients with MSI‐H tumors received less second‐line chemotherapy (15% vs 37%, P  = 0.005). Conclusions: In unselected mCRC patients, MSI‐H and mut BRAF cases were more common than previously reported. Patients with MSI‐H tumors had worse survival, less benefit from chemotherapy, and they differed considerably from recent third‐line immunotherapy trial patients as they were older and most had mut BRAF tumor (non‐Lynch). Abstract : In the general population of metastatic colorectal cancer, microsatellite instability, and BRAF ‐mutated tumors are more common than previously assumed. Unselected patients with microsatellite instability tumors are very different from patients included in the recent third line immunotherapy trials as most of them are BRAF ‐mutated (non‐Lynch), they are older and receive less frequently palliative chemotherapy with limited effects.